Determination of Sustainable Groundwater Conservation Zones Based on Groundwater Recharge Areas: Case Study: Denpasar City - Putu Doddy Heka Ardana; I Wayan Diasa; I Putu Arie Guna Wijaya; Tri Hayatining Pamungkas (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2023)
Groundwater is a valuable resource for meeting the daily needs of humans, which continues to increase along with population growth. Therefore, it is essential to maintain groundwater properly. Groundwater management can be carried out comprehensively in groundwater basins, including determining groundwater recharge areas. This study aims to determine the location of groundwater recharge to conserve groundwater in Denpasar City to create groundwater sustainability. The geospatial analysis uses a weighting and scoring approach (Overlay Weighted Sum) to determine the groundwater recharge area. Retrieval data in the field by observing geological conditions and measuring the depth of the phreatic surface in Denpasar City. The determination of recharge and discharge areas was analyzed using the geospatial method using the ArcGIS 10.8 application using Interpolation Inverse Distance Weighted (IDW). The five parameters used in this scoring assessment are lithology, rainfall, soil cover type, slope, and phreatic surface depth. The highest score obtained from the weighting of the scoring is 46, while the lowest score is 36. The recharge area is found in the weighted value of 41-46, which is in the northern region of Denpasar City. The discharge area is located at a weight value of 36-41 in the southern area of Denpasar City.